The comparison of the effects of intraarticular injections of bovine amniotic fluid and hyaluronic acid on cartilage tissue in an experimental osteoarthritic rabbit model: histopathological and immunohistochemical results - Tanrisever, Murat; Eroksuz, Hatice; Bulut, Sait (Tubitak Scientific & Technological Research Council Turkey, 2017)
In this experimental study, effects of bovine amniotic fluid and hyaluronic acid were compared on an osteoarthritic model induced in rabbit stifle joints. The study was performed on 21 rabbits undergoing anterior cruciate ligament transaction for establishing osteoarthritis. Four weeks later, the rabbits were divided into 3 equal groups of 7 animals each. The first group of rabbits received intraarticular injection of 0.5 mL of bovine amniotic fluid (BAF) three times at 1-week intervals. The second group of rabbits received intraarticular injection of 0.5 mL of hyaluronic acid (HA) three times at 1-week intervals. The third group of rabbits served as a control with no application. Articular surfaces of the femur and tibia were evaluated using the Mankin scoring system for histopathological cartilage examination and were evaluated for immunohistochemical examination by using caspase-3, caspase-8, and MMP-13. All statistical results showed that there were highly significant differences between the control group and the other groups. On the other hand, there was no significant difference between the BAF and HA groups (P < 0.01). It was concluded that the use of BAF, which is an inert fluid rich in growth factors, had protective effects against degenerative cartilage changes in an experimental rabbit model and can be an alternative agent in cartilage protective therapy.
Keywords: Experimental osteoarthritis; hyaluronic acid; bovine amniotic fluid; caspase-3; caspase-8; MMP-13